Elixir : spirits of celebration. - Loong, Cui Wen. (2011)
Elixir: Spirits of Celebration is a project that explores the concept of rebirth and cycles of time through festivals. In our fast paced, highly urbanized cities, where much of our beliefs and perceptions of time are derived from commercial and corporate structures, our lifestyles are directed towards fueling commercial activity. The reasons of celebration and shared rituals for celebrating the natural cycles of harvest have been eroded through time, becoming excuses for more commercial activities that have a disconnect to their spiritual roots, as seen in the great emphasis on universal holidays like Christmas Day celebrations and Chinese New Year in Singapore. What this fyp project aims to do is to discover our first perceptions of festivals in relation to their purpose of charting cycles of time and rebirth; through how the ancients charted time on this same earth, and to show the natural rhythms of meaning that explain the festivities that we celebrate today. In exploring the ancient festivals and how time was viewed in the past, I hope to find the roots of what festivities are all about and to share their richness and original purpose to a modern audience today.